2016
DOI: 10.1002/14651858.cd011033.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological treatment for Buerger's disease

Abstract: Moderate quality evidence suggests that intravenous iloprost (prostacyclin analogue) is more effective than aspirin for eradicating rest pain and healing ischaemic ulcers in Buerger's disease, but oral iloprost is not more effective than placebo. Verylow and low quality evidence suggests there is no difference between prostacyclin (iloprost and clinprost) and the prostaglandin analogue alprostadil for healing ulcers and relieving pain respectively in severe Buerger's disease. Very-low quality evidence suggests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 31 publications
1
39
0
Order By: Relevance
“…In addition to discontinuation of cigarette smoking, only intravenous prostaglandin has demonstrated proven efficacy, but its effect fades upon finishing treatment (21–28 days). [3] More recently, bosentan has been introduced in refractory cases of TAO, bringing in a new alternative for prolonged oral treatment. [915] …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to discontinuation of cigarette smoking, only intravenous prostaglandin has demonstrated proven efficacy, but its effect fades upon finishing treatment (21–28 days). [3] More recently, bosentan has been introduced in refractory cases of TAO, bringing in a new alternative for prolonged oral treatment. [915] …”
Section: Discussionmentioning
confidence: 99%
“…Different treatments such as antiplatelet agents, anticoagulants, and vasodilators (including calcium channel blockers, pentoxyfylline, and cilostazol) are widely used, although there is no proven evidence of their palliative benefits. [3,4] Prostaglandin analogs are beneficial when administered intravenously, although they are no better than placebo on oral administration, and the beneficial effects are transient and disappear after treatment is stopped. [3] Surgical techniques (revascularization, sympathectomy, Ilizavor technique, and omentopexy omentum autografts) are limited in scope and usefulness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to cite the degree of evidence of these treatments. In a recent Cochrane systematic review on the pharmacological treatment of thromboangiitis [36], prostacyclin analog versus placebo, aspirin, and a prostaglandin analog, and folic acid versus placebo were included. Studies that evaluated pharmacological agents such as cilostazol, clopidogrel, and pentoxifylline, or studies that compared oral prostanoid versus intravenous prostanoid were not incorporated because they were not randomized controlled trials.…”
Section: Pharmacological Treatmentmentioning
confidence: 99%
“…Studies that evaluated pharmacological agents such as cilostazol, clopidogrel, and pentoxifylline, or studies that compared oral prostanoid versus intravenous prostanoid were not incorporated because they were not randomized controlled trials. Moderate evidence (one study) suggested that intravenous iloprost was effective in participants with critical limb ischemia (ulcers and rest pain) after 4 weeks of treatment when compared with aspirin, without differences in amputation rates [36]. Two trials indicate that prostacyclin was very effective as prostaglandin analogs in healing ulcers (very low-quality evidence) and extinguishing pain at rest (low-quality evidence), but rates of amputation were not reported by the authors [36].…”
Section: Pharmacological Treatmentmentioning
confidence: 99%